THE RELATIONSHIP BETWEEN SLEEP QUALITY AND COMPUTER VISION SYNDROME IN ADOLESCENT DURING COVID-19 PANDEMIC - Laeto, Arwan Bin; Nurwany, Raissa; Lubis, Dhiyan Handi Asyhari (Indonesian Journal of Health Science, 2024)
Computer Vision Syndrome (CVS) is a group of eye and vision problems caused by long-term use of visual electronics. Since the COVID-19 pandemic, the use of digital devices has increased, resulting in increased ease of exposure to CVS which is feared to disrupt sleep quality. This study aimed to determine the relationship between sleep quality and CVS among adolescents during the COVID-19 pandemic. This research is an observational analytic study with a cross-sectional design using primary data. Data were taken through a questionnaire with a sample of 96 adolescents who met the inclusion and exclusion criteria. Data analysis was carried out with the Chi-Square test. In this study, the results showed that the quality of sleep in adolescents had a prevalence of 59,4% as well as the prevalence of adolescents diagnosed with CVS by 56,3%. There is a statistically significant relationship between sleep quality and CVS with a p-value of 0,001. There is a high prevalence of poor sleep quality and CVS among adolescents. CVS is significantly related to sleep quality.Â  The implication of this result is that can impact academic performance and exacerbate the symptoms of CVS, such as eye strain, blurred vision and headaches